HUBUNGAN INTENSITAS KEBISINGAN DENGAN TINGKAT STRES KERJA PADA PEKERJA AREA WORKSHOP PT. BINTANG INTIPERSADA HIPYARD BATAM - Andi Ipaljri Saputra; Miralza Diza (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2019)
Noise sources can be found in the work environment. Physical stressors such as noise can cause various health problems. One of the psychological disorders found as a result of noise is work stress. PT. Bintang Intipersada has a fairly high noise intensity. So the researchers wanted to find the relationship of noise intensity with work stress levels in workers. This research method was observational analytic with a cross-sectional approach conducted at PT. Bintang Intipersada Shipyard Batam. The sampling technique was purposive sampling with a population of 100 workers in 2019 and obtained the results of 61 workers determined by the inclusion and exclusion criteria. The results of the study were analyzed using the Spearman test. The results of this study found that workers who were exposed to noise intensity ≤85 dBA and experienced mild work stress by 15 (68.2%) people, workers who were exposed to noise intensity ≤85 dBA and experienced moderate work stress by 5 (22.7% ) people, then workers who are exposed to noise intensity ≤85 dBA and experience heavy work stress as much as 2 (9.1%) people. Whereas workers who were exposed to noise intensity> 85 dBA and experienced light work stress by 3 (7.7%) people, workers who were exposed to noise intensity> 85 dBA and experienced moderate work stress by 9 (23.1%) people, then workers exposed to noise intensity> 85 dBA and experiencing heavy work stress as many as 27 (69.2%) workers. Spearman analysis results obtained significance value p = 0,000. This figure is significant because the p-value is smaller than the significance level (α) = 5% (0.05). Correlation value (r) is 0.667 which means strong correlations. So it can be concluded that there is a strong and meaningful relationship between noise intensity with work stress levels. Based on this study it can be concluded that there is a significant relationship between noise intensity with the level of work stress on workers.